2019
DOI: 10.1002/aoc.4898
|View full text |Cite
|
Sign up to set email alerts
|

A family of functional Ln‐organic framework constructed by iodine‐substituted aromatic polycarboxylic acid for turn‐off sensing of UO22+

Abstract: With the rapid development of nuclear energy, one of the main constraints restricting the development of nuclear energy is the long‐term safe disposal of strong uranium waste. Here it is a great significance that we use four new synthetic Ln (III)‐based coordination polymers to test the uranium solution. In this study, four three‐dimensional coordination polymers 1–4 (CPs‐(1–4); Ln = Eu, Gd, Sm, Nd) were successfully synthesized through 1:1 complexation of Ln (NO3)3·6H2O with poly‐carboxylic acid ligand H3TIBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Currently, metal–organic frameworks with adjustable pores and functional species in their structures have been widely used for storage, separation, delivering biomedicine, luminescent sensing, etc. With regard to the detection of uranium, a series of lanthanide organic frameworks constructed by iodine-substituted aromatic poly­(carboxylic acid) have been reported with the detection limit of 5.54 mg/L . A water-stable Tb­(III)-MOF showed the turn-off sensing of uranyl ions with the detection limit of 0.9 μg/L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, metal–organic frameworks with adjustable pores and functional species in their structures have been widely used for storage, separation, delivering biomedicine, luminescent sensing, etc. With regard to the detection of uranium, a series of lanthanide organic frameworks constructed by iodine-substituted aromatic poly­(carboxylic acid) have been reported with the detection limit of 5.54 mg/L . A water-stable Tb­(III)-MOF showed the turn-off sensing of uranyl ions with the detection limit of 0.9 μg/L .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the detection of uranium, a series of lanthanide organic frameworks constructed by iodinesubstituted aromatic poly(carboxylic acid) have been reported with the detection limit of 5.54 mg/L. 33 A water-stable Tb(III)-MOF showed the turn-off sensing of uranyl ions with the detection limit of 0.9 μg/L. 34 Additionally, some MOF materials also found potential application in the uranium adsorption and separation.…”
Section: Introductionmentioning
confidence: 99%
“…(j) Its fluorescence intensity curve for different concentrations of uranium solution. Reproduced with permission from ref ( 138 ). Copyright 2019 Wiley.…”
Section: Mof-based Materials For Uranium Detectionmentioning
confidence: 99%
“…(2) Introduction of a halogen atom into the aromatic ring to form a halogen bond may increase the size and change electron cloud density of the organic skeleton. 44 On the basis of our research idea described above, we have reported several lanthanide metal MOFs, including (i) [Ln(TIBTC)(DMF) 3 ] n (Ln = Eu, Gd, Sm, or Nd) 45 After the mixture had been stirred, 3 mL of concentrated H 2 SO 4 was added dropwise. The mixture was heated to reflux at 90 °C for 10 h, filtered with a vacuum line, repeatedly washed with distilled water, purified with solvent acetone, and suction filtered to yield 2,4,6-triiodo-1,3,5-trimethylbenzene (M-1) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Introduction of a halogen atom into the aromatic ring to form a halogen bond may increase the size and change electron cloud density of the organic skeleton . On the basis of our research idea described above, we have reported several lanthanide metal MOFs, including (i) [Ln­(TIBTC)­(DMF) 3 ] n (Ln = Eu, Gd, Sm, or Nd) and (ii) [Pr­(TIBTC)­(DMF) 3 ] n (H 3 TIBTC = 2,4,6-triiodo-1,3,5-benzenetricarboxylic acid). In this work, as a part of our continued research, we developed four new transition metal coordination complexes, [Zn­(TIBTC)­(DMA)]·[NH 2 (CH 3 ) 2 ] ( 1 ), [Cd (TIBTC)­(H 2 O)]·[NH 2 (CH 3 ) 2 ]·DMA ( 2 ), [Cd 2 (TIBTC)­(2,2′-bipy) 2 (HCOO)] ( 3 ), and [Cd 2 (DIBTC)­(2,2′-bipy) 2 (HCOO)] ( 4 ) under solvothermal conditions, and preliminarily explored their fluorescence properties to detect thiamine hydrochloride, NACs, and Fe 3+ /Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%